Mendelian randomization analysis: The causal relationship between C-reactive protein and amyloidosis and between C-reactive protein and atherosclerosis - Chunhui Liu; Xupeng Huang; Yongsheng Huang; Hongguang Jin (PLoS ONE, 2025)
Background A number of studies have shown that elevated CRP is linked to AS and reduced CRP is linked to amyloidosis. However, the exact mechanism explaining this connection is not known. Methods We used genomic pooled data from the Genome-Wide Association Study (GWAS) in a two-sample, two-way Mendelian randomization (MR) analysis study. Methods used included inverse variance weighting (IVW), weighted median (WM), MR-Egger method, Cochran’s Q, MR-PRESSO, MR-Egger intercept test, and leave-one-out sensitivity analysis. To investigate the specific causal relationship between C-reactive protein and amyloidosis and between C-reactive protein and atherosclerosis (coronary, cerebral, aortic, and peripheral atherosclerosis). The study procedure was performed with the STROBE-MR checklist. Results There was a inverse association between C-reactive protein and amyloidosis and an positive causal relationship between C-reactive protein and aortic atherosclerosis. The development of aortic atherosclerosis was positively correlated with C-reactive protein levels (IVW:p = 0.003, OR=1.203,95% CI:1.066–1.358). Whereas amyloidosis onset was associated with reduced C-reactive protein levels (IVW:p = 0.022, OR=0.582,95% CI:0.366–0.924). Reverse Mendelian randomization analysis found no evidence of reverse causality. Conclusion We verified the existence of a negative association between C-reactive protein and amyloidosis and a positive association between C-reactive protein and atherosclerosis by Mendelian randomization, which may provide some reference value for subsequent studies and treatment in the clinic.